1993
DOI: 10.5636/jgg.45.805
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Induction in South-West Nigeria: Analogue Model and Field Results.

Abstract: Electromagnetic induction in the south-west region of Nigeria is studied by comparing laboratory analogue model measurements with observations at eleven field sites. The scaled laboratory model simulates the ocean bathymetry and the coastlines in the region. Model magnetic fields for simulated periods of 20, 30, and 60 min for two mutually perpendicular polarizations of a uniform horizontal source field were used to obtain the in-phase and quadrature induction arrows. The model results show the typical coast e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…It was demonstrated that even for such major conductors the ocean responses could be subtracted successfully, and that the behaviour of the difference arrows was highly period and location dependent, with the quadrature and in-phase components at given periods differing from each other considerably from site to site. Figure 8 shows the model and the field site in-phase and quadrature induction arrows at 20 min at eleven sites in Nigeria discussed previously by Kang et al (1993). The solid and dashed arrows in Fig.…”
Section: Application To Geomagnetic Measurements In Coastal Nigeriamentioning
confidence: 99%
See 4 more Smart Citations
“…It was demonstrated that even for such major conductors the ocean responses could be subtracted successfully, and that the behaviour of the difference arrows was highly period and location dependent, with the quadrature and in-phase components at given periods differing from each other considerably from site to site. Figure 8 shows the model and the field site in-phase and quadrature induction arrows at 20 min at eleven sites in Nigeria discussed previously by Kang et al (1993). The solid and dashed arrows in Fig.…”
Section: Application To Geomagnetic Measurements In Coastal Nigeriamentioning
confidence: 99%
“…The sites that warrant further consideration are BAD, IKD, AGB, EJI, and OKI. In the earlier work (Kang et al, 1993), the behaviour of the arrow at BAD was considered rather erratic with changing period (periods of 20, 30, 60 min), and since some measurements were known to be in error, no attempt was made to interpret the observations. However, noting that BAD is situated between a pair of grabens (GI and G2), the fact that the in-phase response at 20 min is negligible while the quadrature response is large with the arrow pointing towards graben Gl, is quite plausible, particularly when it is realized that the more distant graben G3 would also have an effect at BAD, and at 20 min the in-phase response of Gl to the west could very well be cancelled by the combined responses of G2 and G3 to the east of BAD, while the quadrature response could be showing G2 as providing the major contribution.…”
Section: Application To Geomagnetic Measurements In Coastal Nigeriamentioning
confidence: 99%
See 3 more Smart Citations